2017
DOI: 10.1002/em.22163
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and mutagenic properties of Ni and NiO nanoparticles investigated by comet assay, γ‐H2AX staining, Hprt mutation assay and ToxTracker reporter cell lines

Abstract: Nickel (Ni) compounds are classified as carcinogenic to humans but the underlying mechanisms are still poorly understood. Furthermore, effects related to nanoparticles (NPs) of Ni have not been fully elucidated. The aim of this study was to investigate genotoxicity and mutagenicity of Ni and NiO NPs and compare the effect to soluble Ni from NiCl2. We employed different models; i.e., exposure of (1) human bronchial epithelial cells (HBEC) followed by DNA strand break analysis (comet assay and γ‐H2AX staining); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 28 publications
8
58
0
Order By: Relevance
“…Previous studies indicated the NiO-NPs caused damage in lung and liver and induce pulmonary inflamations via reactive oxygen species (ROS) (Chang et al, 2017;Li et al, 2018;Marzban et al, 2017;Senoh et al, 2017;Shinohara et al, 2017;Yu et al, 2017;Dumala et al, 2018;Ogami et al, 2009). In vitro researches confirmed with the in vivo studies that the NiO-NPs induced an increase in ROS and caused oxidative damage in the cells (Abudayyak et al 2017a;Åkerlund et al, 2018;Di Bucchianico et al, 2018;Mohamed et al, 2018;Saquib et al, 2018). Previous data confirmed with our results; oxidative stress could be the mechansim underlying the cytoand genotoxicity induced by the NiO-NPs .…”
Section: Tablesupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies indicated the NiO-NPs caused damage in lung and liver and induce pulmonary inflamations via reactive oxygen species (ROS) (Chang et al, 2017;Li et al, 2018;Marzban et al, 2017;Senoh et al, 2017;Shinohara et al, 2017;Yu et al, 2017;Dumala et al, 2018;Ogami et al, 2009). In vitro researches confirmed with the in vivo studies that the NiO-NPs induced an increase in ROS and caused oxidative damage in the cells (Abudayyak et al 2017a;Åkerlund et al, 2018;Di Bucchianico et al, 2018;Mohamed et al, 2018;Saquib et al, 2018). Previous data confirmed with our results; oxidative stress could be the mechansim underlying the cytoand genotoxicity induced by the NiO-NPs .…”
Section: Tablesupporting
confidence: 91%
“…In positive controls (100 µM H2O2), the tail intensities were 13.3% (1.85 fold). Previously, researchers showed that the NiO-NPs could induce DNA damages in different cells (Abudayyak et al 2017a;Ahamed, 2011;Ahamed et al, 2013;Ahmad et al, 2013;Åkerlund et al, 2018;Chang et al, 2018;De Carli et al, 2018;Di Bucchianico et al, 2018;Horie et al, 2011;Lee et al, 2015;Siddiqui et al, 2012). Dumla et al (2017) reported significant DNA damages in liver, lung and kidneys of rats exposed orally.…”
Section: Figurementioning
confidence: 99%
“…Of the NPs tested, Mn and Mn 3 O 4 NPs caused by far the largest activation of the Srxn1-GFP reporter resulting in around 20-fold maximum increase compared with control ( Figure 4). The Sn, Sb 2 O 3 and Sb NPs were also active, inducing approximately a 7-10 fold increase (Figure 4), which is comparable to previous observations for Ni and NiO NPs [11], and for Co and CoO NPs [12]. Some induction (2.5 and 2.7-fold) was also observed for the V 2 O 5 and Ag NPs, respectively (Figure 4 and Supplementary Table S1).…”
Section: Oxidative Stress-many Nps and All Qds Induce Reporters Relatsupporting
confidence: 88%
“…Finally, this gene mutation assay has also been used to detect the mutagenic potential of nickel oxide NPs. In that case, a small but statistically significant increase in the frequency of Hprt mutations was observed for NiO NPs but only at one of the different tested doses [21].…”
Section: Discussionmentioning
confidence: 86%
“…The most commonly used target genes for measuring the induction of mutations in mammalian cells are the thymidine kinase (Tk) and the hypoxanthine guanine phosphoribosyl transpherase (Hprt) genes. Specifically, the Hprt mutation assay has already been successfully applied to the evaluation of different nanomaterials [6,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%